Bridging Explainability and Interpretability in AI-driven SCM Projects to Enhance Decision-Making - El Oualidi Taoufik; Assar Saïd (ITM Web of Conferences)
New AI-based systems implementation in companies is steadily expanding, paving the way for novel organizational sequences. The increasing involvement of end-users has also garnered interest in AI explainability. However, AI explainability continues to be a serious concern, particularly in conventional fields of activity where end-users play an essential role in the large-scale deployment of AI-based solutions. To address this challenge, managing the close relationship between explainability and interpretability deserves particular attention to enable end-users to act and decide with confidence.